The use of the in vitro micronucleus assay on the genotoxicity assessment of cellulose nanofibrils in mammalian cell lines - Ventura, Célia (2020)
With the expansion of innovative cellulose nanofibrils (CNF) applications, either for industrial (e.g., paper industry) or biomedical purposes (e.g., tissue regeneration and dentistry), human exposure has been increasing, raising concerns about their potential health outcomes . Being persistent high aspect-ratio nano-objects, CNFs effects may resemble those of some multi-walled carbon nanotubes, e.g., the MWCNT-7, which has been reported to induce chromosome instability, cytoskeleton alterations and dysfunction of several cancer-related cell signaling pathways . The in vitro cytokinesis-block micronucleus (CBMN) assay is a sensitive and reliable assay for analysis of chromosome damage in mammalian cells, with the potential of providing mechanistic information and predicting carcinogenic effects. In this work we evaluated the use of the CBMN assay in different mammalian cell systems to characterize the genotoxicity of a CNF produced from an industrial bleached Eucalyptus globulus kraft pulp through TEMPO-mediated oxidation followed by a high-pressure homogenization process . The CNF sample was fully characterized in order to assess the most relevant physicochemical properties. It presented a wide distribution of diameters, with the mode in the 20–25 nm range and a length of several micrometers. Preliminary doserange finding through assessment of the cytotoxic effects (MTT and clonogenic assays) in cell lines representative of the respiratory tract (A549, A549 co-cultured with macrophage-like THP-1 cells and V79 cells) and bone (MG63 osteoblasts) showed that the CNF was not cytotoxic, regardless of the exposure period. The results of the CBMN assay (following OECD guideline 487) showed that exposure to low CNF concentrations induced a significant increase of micronuclei in co-cultured alveolar (A549) cells and in osteoblasts, while no significant effect was observed in A549 cells in monoculture. These results support the suitability of the in vitro micronucleus assay to assess the genotoxicity of nanofibers like CNF, highlighting the relevance of the cell system selected. This and other factors related to the experimental design are discussed, pointing to the need of nano-specific guidelines for this assay application in nanogenotoxicology. References Ventura et al. 2020. Cellulose, DOI 10.1007/s10570-020-03176-9 Ventura et al. 2020. Nanotoxicology, 14:479 Ventura et al.2020. Toxicol Lett, 328: 7 Fenech, M. 2007. Nature Protocols 2: 1084. Lourenço et al. 2017. Cellulose 24: 349.